FASILITASI TEMPAT BELAJAR WIRAUSAHA: UPAYA PENINGKATAN MOTIVASI DAN PELUANG KERJA DI PEDESAAN (Studi Kasus pada Karang Taruna Sribitan "Amusri") - Masduki Zakaria, Umul Aiman, Bambang Sriwijaya, (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2014)
Sribitan IX which located in Bangunjiwo village has hilly topographiccountour that marginal soil. Most of the recident on sribitan village are in a notgood economical condition. About 51 families of the 282 families are poor.13.74% recident not finishing their elementary school, and 36.72% recidents arenot finishing their study on high schol grade and 21.8% recidents are unemployed.Most on the women are joblesss and some of the man arelabour andfarmer. Sribitan has youth organisation" AMUSRI" with 40 members thatconsist of senior and junior high school students, university student,and marriedyoung couple.Transfer of knowledge and technology is done with counseling, practicing,demplot, and comparative studying. Many kind of activity that give toparticipants on this program such as catfush farming, worm farming, verticaltureand producing instan beverages from fruits and spices.Yield of this submission are improving member of Amusri motivation toutilize the land, using their spare time to study, improving entrepeunerhip skill,and making Amusri member became more harmouniuos.